The Importance of The Ijoza System in The Process of Teaching and Education by Mahmud Zamakhshari - Akhter Muhammad Rahim (TADRIS: Jurnal Pendidikan Islam, 2020)
This article is based in one of the scientific legacies by Mahmud Zamakhshari on the work on spiritual education and morality "Atvaq uz-zahab fil-mawo'iz val-khutab" ("Golden Necklaces of teachings and exhortations") and the transmission of knowledge, the exhortation to know its documents and evidence. Az-Zamahshari's request for knowledge refers to his travels to Bukhara, Khorasan, Damascus, Iraq, and the Hijaz, where he received permission from his teachers for various books and sciences, as well as the permission given by the scholar to many of his students. At the same time, a sample of Zamakhshari's authorized letters (letters ijaza) is given. At the end of our article, we will focus on some important and necessary golden advices in the spiritual education of students from the work of the great scholar Mahmud Zamakhshari "Atvaq uz-zahab fil-mawaiz val-khutab".Â